Doping Portland Cement with Natural Clay and Bauxite Mineral Additives from Débélé: Effects on the Mechanical Strength of Mortars - Balde, Mamadou Yaya; Kepdieu, Jean Marie; Tchanang, Gustave; Baldé, Souleymane; Djangang, Chantale Njiomou (European Journal of Applied Sciences, 2024)
In the course of this experimental work, which led to the substitution of Portland cement by 20% by mass of mineral additives, the mechanical compressive strength of hybrid cements was evaluated at different ages: 7, 28, 42 and 90 days. The effect of bauxite on the development of mechanical strength was also assessed. The study showed that the hybrid cements obtained had appreciable mechanical strengths, with values ranging from 14 to 34.6 MPa for the series of mortars containing a single additive, compared with 15 to 36.4 MPa for hybrids containing two mineral additives. This study demonstrated the positive effect of adding raw bauxite powder to the cementitious medium, resulting in an increase in mechanical strength from 6.59% to 42.31% when the quantity of B varied from 5 to 15% for the B-Ab hybrids. In the B-Ar series, this increase ranged from 6 to 29.83%. The mechanical performance of the composite cements obtained means that they can be used in a variety of masonry applications, in compliance with technical construction standards in a difficult economic context.